International Capital Markets : Developments and Prospects, 1983 - Lipsky, John.; Keller, Peter; Mathieson, Donald; Williams, Richard (Washington, D.C. : International Monetary Fund, 1983)
This paper provides a description and analysis of recent developments in international capital (banking and bond) markets and an assessment of market conditions and prospects for financing flows, in particular.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet